532 nm Sub Pulsed laser for treating Melasma in Latin American Patients, series of cases - Perez Willis, Kateryn (Aesthetic Medicine, 2025)
Objective: to analyze a series of cases treated with a 532 nm Sub Pulsed laser treatment for Melasma in Latin American Patients with Fitzpatrick type IV. Background: melasma is a common, acquired, symmetrical hypermelanosis that presents as light to dark brown macules on the face usually over the forehead and malar areas that negatively impact patient’s quality of life. Various laser treatments have been described without any consensus, however targeting the vascular component has been progressively gaining popularity, but adverse reactions such as transient post inflammatory hyperpigmentation or atrophic scars have been described for treating superficial and deep vessels. We propose a new laser range to treat Melasma. Methods: this is an observational study with 20 patients, Fitzpatrick type IV diagnosed with mixed type facial melasma that were treated with one to two sessions of a Sub Pulsed 532 nm Laser with an interval of 11 to 30 days. Dermoscopy was performed in the patients before the laser to show the presence of multiple vessels and pigmentation in the patients, before and after pictures were taken with Quantificare Lifeviz to show the results after the laser without any other topical or oral treatment. Results: in this series of cases the Modified MASI Score describes an average of 90.9% improvement in Melasma severity after the laser sessions. The pictures taken with Quantificare Lifeviz to assess the vascular, pigmentary and basal pictures show significant improvement. No PIH (Post inflammatory Hyperpigmentation) or major adverse reaction was described in this study.